Pancasila Student Profile Strengthening Project Module Development Training Anti-Bullying: Pelatihan Pengembangan Modul Proyek Penguatan Profil Pelajar Pancasila anti Bullying - Sulistyosari*, Yunike; Hasmy, Zulfauzy Abu; Tinambunan, Medi; Putra, Andi Andre Pratama (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Pancasila student profile strengthening project is a new program in the Merdeka Curriculum which is a challenge for schools. The problem for teachers in North Sulawesi is the lack of understanding of teachers in implementing the Pancasila student profile strengthening project, especially in developing modules. So that the development of the Pancasila Student Profile Strengthening Project (P5) teaching module in schools is a need for P5 facilitators in implementing P5. Another problem is the rampant bullying cases in every class. This prompted a community service by a team from Manado State University. The community service was carried out in August 2024 in the hall of SMP N 3 Tondano. This training uses lecture and demonstration methods with the aim of providing teachers with P5 development strategies and anti-bullying education for teachers, before the implementation of P5 anti-bullying. This activity begins with a pretest and ends with a posttest, the first training session is bullying material followed by module development training using the backward design strategy. This backward design begins with determining project objectives, determining assessments and continuing with the preparation of teaching materials that support the achievement of project objectives. The training results showed an increase in knowledge of 0.7 based on the N-Gain formula, which indicates an increase in knowledge in the moderate category on the topic of anti-bullying in the context of P5. This activity is expected to be a provision for teachers in implementing the P5 theme of building the soul and body, so that P5 activities can create skills in students and instill characters that are in line with Pancasila values. Making students aware of the dangers of bullying, so that schools that are safe from bullying can be created.